Evaluating patient participation in value‐based healthcare: Current state and lessons learned - Henrike J. Westerink; Mirjam M. Garvelink; Cornelia F. vanUden‐Kraan; Ouisam Zouitni; Hans A. J. Bart; Philip J. van derWees; Paul B. van derNat; the Santeon Patient Participation Study Group (Wiley, 2024)
Abstract Introduction Value‐based healthcare (VBHC) focusses on increasing value for patients. Hospitals aim to implement VBHC via value improvement (VI) teams for medical conditions. To determine the patient's perspective on value, collective patient participation is important in these teams. We therefore evaluated the current state of patient participation in VI teams and share lessons learned. Methods This mixed‐methods study was conducted at seven collaborating hospitals in the Netherlands. A questionnaire (the public and patient engagement evaluation tool) was tailored to the study's context, completed by VI team members (n = 147 from 76 different VI teams) and analysed with descriptive statistics. In addition, 30 semistructured interviews were held with VI team members and analysed through thematic analysis. Data were collected between February 2022 and January 2023 and were triangulated by mapping the quantitative results to the interview themes. Results Thirty‐eight of the 76 included VI teams reported using a form of patient participation. Many respondents (71%) indicated a lack of a clear strategy and goal for patient participation. Multiple VI team members believed that specific knowledge and skills are required for patients to participate in a VI team, but this led to concerns regarding the representativeness of participating patients. Furthermore, while patients indicated that they experienced some level of hierarchy, they also stated that they did not feel restricted hereby. Lastly, patients were satisfied with their participation and felt like equal VI team members (100%), but they did mention a lack of feedback from the VI team on their input. Conclusion The results imply the lack of full implementation of patient participation within VI teams. Guidelines should be developed that provide information on how to include a representative group of patients, which methods to use, how to evaluate the impact of patient participation, and how to give feedback to participating patients. Patient and Public Contribution Two patient advisors were part of the research team and attended the research team meetings. They were involved as research partners in all phases of the study, including drafting the protocol (e.g., drafting interview guides and selecting the measurement instrument), interpreting the results and writing this article.